Newborn Weight Loss as a Predictor of Persistence of Exclusive Breastfeeding up to 6 Months - Enrica Delfino; Luca Peano; Roberto Giorgio Wetzl; Maria Lorella Giannì; Maria Lorella Giannì; Roberta Netto; Alessandra Consales; Maria Enrica Bettinelli; Daniela Morniroli; Daniela Morniroli; Francesca Vielmi; Fabio Mosca; et al. (Frontiers Media S.A., 2022)
ObjectivesTo investigate the association between neonatal weight loss and persistence of exclusive breastfeeding up to 6 months.Study DesignAn observational cohort study in the setting of a Baby Friendly Hospital, enrolling 1,260 healthy term dyads. Neonatal percentage of weight loss was collected between 48 and 72 h from birth. Using a questionnaire, all mothers were asked on the phone what the infant's mode of feeding at 10 days, 42 days and 6 months (≥183 days) from birth were. The persistence of exclusive breastfeeding up to 6 months and the occurrence of each event that led to the interruption of exclusive breastfeeding were verified through a logistic analysis that included 40 confounders.ResultsInfants with a weight loss ≥7% were exclusively breastfed at 6 months in a significantly lower percentage of cases than infants with a weight loss <7% (95% CI 0.563 to 0.734, p < 0.001). Weight loss ≥7% significantly increases the occurrence of either sporadic integration with formula milk (95% CI 0.589 to 0.836, p < 0.001), complementary feeding (95% CI 0.460 to 0.713, p < 0.001), exclusive formula feeding (95% CI 0.587 to 0.967, p < 0.001) or weaning (95% CI 0.692 to 0.912, p = 0.02) through the first 6 months of life.ConclusionsWith the limitations of a single-center study, a weight loss ≥7% in the first 72 h after birth appears to be a predictor of an early interruption of exclusive breastfeeding before the recommended 6 months in healthy term exclusively breastfed newborns.